2001
DOI: 10.1046/j.1365-2206.2001.00202.x
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ perceptions of their children in a context of shared political uncertainty

Abstract: The study describes the differences and similarities between parents’ feelings and their perception of their children’s feelings in a politically uncertain situation. The study focuses on Israeli families living in Judaea and Samaria (the West Bank) during two periods: the Intifada and the post‐Oslo Agreements years during the first phase of the peace process with the Palestinians. The research combines qualitative and quantitative methods. The results show that most of the feelings evoked by the uncertainty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
16
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 14 publications
4
16
0
Order By: Relevance
“…Similar emotions were noted by Shamai (2001) among Israeli parents who were living in the West Bank during the period of political uncertainty following the Oslo Accords. In the current study, the mothers' various efforts to protect their children physically and their constant calculations and decisions about where and where not to take them were based on the idea that if they did this and avoided that, they could provide their children with some measure of protection from physical harm.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Similar emotions were noted by Shamai (2001) among Israeli parents who were living in the West Bank during the period of political uncertainty following the Oslo Accords. In the current study, the mothers' various efforts to protect their children physically and their constant calculations and decisions about where and where not to take them were based on the idea that if they did this and avoided that, they could provide their children with some measure of protection from physical harm.…”
Section: Discussionsupporting
confidence: 56%
“…Furthermore, a clear and robust association was revealed between increased symptoms in children and poor psychological functioning in their mothers (Laor, Wolmer, & Cohen, 2001). Along similar lines, Shamai (2001) found, in a quantitative and qualitative study of Israeli families who were living in the West Bank, a preponderance of negative emotions-namely, fear, anger, hate, avoidance, and a desire for revenge-among both parents and children and a close association between the emotions reported by the parents and their children. Koplewicz et al (2002), studied children who had been on a class trip to the World Trade Center in New York City and their mothers when it was bombed in 1993 and found that some of the mothers developed posttraumatic stress disorder, even though they themselves had not physically been there.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Most of the existing knowledge describes the disruption in family routine due to the war-related situation and its effect on increasing teenagersÕ distress. These studies identified the family as a core element of childrenÕs and adolescentsÕ resilience (Cairns & Dawes, 1996;Gabarino & Kostelny, 1996a;b;Garbarino, Kostelny, & Dubrow, 1991;Shamai, 2001Shamai, , 2002. The study of Garbarino and Kostelny (1996) argues that children and teenagers can cope with political violence if they face it in the context of a functioning family system.…”
Section: Social Systems As Resources Of Coping With Stressmentioning
confidence: 97%
“…Most of the existing knowledge points to the disruption in family routine due to the war-related situation and its effect on increasing teenagers' distress. These studies identify the family as a core element of children's and adolescents' resilience (Cairns & Dawes, 1996;Shamai, 2001Shamai, , 2002. Garbarino and Kostelny (1996a) argue that children and teenagers can cope with political violence if they face it in the context of a functioning family system.…”
Section: The Effects Of Terrorism On Israeli Children and Youthmentioning
confidence: 97%